Peptide OPTX-1 From Ornithodoros papillipes Tick Inhibits the pS273R Protease of African Swine Fever Virus - Wang, Jingjing; Ji, Mengyao; Yuan, Bingqian; Luo, Anna; Jiang, Zhenyuan; Zhu, Tengyu; Liu, Yang; Kamau, Peter Muiruri; Jin, Lin; Lai, Ren (Frontiers in Microbiology, 2021)
African swine fever virus (ASFV) is a large double-stranded DNA virus and causes high mortality in swine. ASFV can be transmitted by biological vectors, including soft ticks in genus Ornithodoros but not hard ticks. However, the underlying mechanisms evolved in the vectorial capacity of soft ticks are not well understood. Here, we found that a defensin-like peptide toxin OPTX-1 indentified from Ornithodoros papillipes inhibits the enzyme activity of the ASFV pS273R protease with a Ki=0.821 ± 0.526 μM and shows inhibitory activity on the replication of ASFV. The analogs of OPTX-1 from hard ticks show more inhibitory efficient on pS273R protease. Considering that ticks are blood sucking animals, we tested the effects of OPTX-1 and its analogs on the coagulation system. At last, top 3D structures represented surface analyses of the binding sites of pS273R with different inhibitors were obtained by molecular docking based on known structural information. In summary, our study provides evidence that different inhibitory efficiencies between soft tick-derived OPTX-1 and hard tick-derived defensin-like peptides may determine the vector and reservoir competence of ticks.